2013
DOI: 10.1149/2.029401jes
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cycling Stability of Lithium Electrodes in Rechargeable Lithium Batteries

Abstract: Poly(3,4-ethylenedioxythiophene)-co-poly(ethylene glycol) copolymer was coated onto lithium metal as a protective layer. The thin conductive polymer with strong adhesion to the lithium electrode suppressed the corrosion of the lithium metal and stabilized the interface of the lithium electrode in prolonged contact with the organic electrolyte. The conductive polymer coating on the lithium metal caused the capacity retention of the Li/LiCoO2 cell to increase from 9.3% to 87.3% after 200 cycles compared to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 39 publications
1
44
0
1
Order By: Relevance
“…Alternatively, ex situ coated mechanically stable artificial layers, such as polymer or solid‐state blocking layers, have been proposed to block the dendrite penetration. These interfacial layers stabilize the interface of the lithium anode with the liquid electrolytes, leading to improved Coulombic efficiency and safety.…”
Section: Possible Solutions and Some Concerns For More Reliable Li‐s mentioning
confidence: 99%
“…Alternatively, ex situ coated mechanically stable artificial layers, such as polymer or solid‐state blocking layers, have been proposed to block the dendrite penetration. These interfacial layers stabilize the interface of the lithium anode with the liquid electrolytes, leading to improved Coulombic efficiency and safety.…”
Section: Possible Solutions and Some Concerns For More Reliable Li‐s mentioning
confidence: 99%
“…It has been shown that both the separation of surface lithium fl akes and the continuous growth of an unstable solid electrolyte interphase layer (SEI) lead to reduction in capacity during cycling. [ 37,54,[106][107][108][109][110] Therefore, unless properly protected [ 4,111 ] and/or combined with a suitable electrolyte, lithium metal cannot be proposed as an …”
Section: The Anodementioning
confidence: 99%
“…To solve these defects, some conductive polymers and fast ionic conductor materials were widely used as surface coating layer on the cathode active materials. [24][25][26][27][28][29][30] materials is coated with various amount of LBO glass via a simple wet chemical process followed by heat-treatment. As expected, the LBO coated materials exhibit obvious improvement both in electrochemical performances and thermal stability under high voltage.…”
Section: Introductionmentioning
confidence: 99%